Factors Associated with Outpatient Loyalty in Hospital: Systematic Literature Review - Muhammad Tsany Saadi; Purnawan Junadi (Eduvest - Journal of Universal Studies, 2024)
The healthcare industry is undergoing a paradigm shift towards patient-centered care. In this competitive environment, patient satisfaction and loyalty are crucial for hospitals. While patient satisfaction is routinely measured, its precise relationship with loyalty remains unclear, as existing studies have yielded mixed results. Other determinants aside from patient satisfaction may also influence patient loyalty. By identifying these key determinants, hospitals can develop targeted strategies to enhance patient satisfaction and promoting patient loyalty, ultimately securing a competitive advantage. Objective: This systematic literature review aims to explore the current research on factors influencing outpatient loyalty to hospitals. Method: This systematic review uses Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A search strategy was used to identify relevant studies in PubMed, ProQuest, and ScienceDirect. The search timeframe encompassed publications between January 2019 and April 2024. A set of predefined inclusion and exclusion criteria were applied, resulting in the identification of 17 articles relevant for further analysis. Result: Patient satisfaction emerged as a key driver of loyalty, positively influenced by factors beyond service quality. These factors include trust in the hospital, word of mouth, hospital image, strong patient-physician relationships, patient convenience, patient motives, switching cost, customer relationship management, and staff kindness and consideration. Conclusion: Patient loyalty is influenced by a multitude of factors extending beyond service quality and satisfaction. Building trust, nurturing patient relationships, optimizing the patient experience, and offering value are crucial considerations. Tailoring strategies to specific patient demographics and cultural contexts are essential.